Knowledge and Attitude of A Sample of Iraqi Doctors about Breaking Bad News To Patients In Baghdad Teaching Hospital and Specialized Surgical Hospital In Medical City - Hussein Kadhim, Shahad; Salih Ismael, Nibras (South Asian Journal of Social Sciences and Humanities, 2025)
Background: Bad news is any bad, sad, or significant information that negatively alters people’s expectations or perceptions of their present or Future. Objectives: to explore the level  of knowledge and attitude toward Break bad news to patients among sample of Iraqi doctors. Methods: A cross-sectional study was conducted at Baghdad teaching hospital and specialized  surgical hospital in Baghdad Medical City from first of January 2019 till end of July 2019. A  convenient sample of 300 Iraqi doctors (resident, specialists, and consultants) participated; they were selected through random sampling, and data were collected by using a self administered questionnaire adopted from a previous study with some modifications. Results: A total of 300 doctors included in this study, males were 158 (52.7%) while females were  142(47.3). The majority of participants were resident form 194(64.7%). The training status of  doctors revealed that the majority of them 204(68.0%) had not been trained about breaking bad  news while only 96(32%) of doctors included in a training course, about 28(29.2%) received  the course during undergraduate while the rest 68(70.8%) received it during postgraduate.  Conclusion and Recommendations: Only one third of them participate in training course  about it. Doctors who received training course undergraduate have better score. The overall  attitude score was fair and its associated with medical degree, consultant doctors get better  attitude score. The study recommends that the Medical College should present educational  courses on how to break bad news to undergraduate students during clinical years.
Keywords: Knowledge; Attitude; Iraqi doctors; breaking bad news; Baghdad Teaching Hospital.